The Applicability of Article 4 Of Anti-Corruption Law And The Theory Of Tort - Didik Endro Purwoleksono (Universitas Airlangga, 2019)
Article 4 of the Indonesian Corruption Law stipulates that the return of state financial losses does not eliminate the criminalization of the perpetrators of criminal acts as referred to in Article 2 and Article 3. What about the suspects or defendants who return the results of corruption related to the theory illegitimacy? There are two theories about the illegitimacy which are; the theory of illegitimacy against the formal law and the theory of illegitimacy against the material law. The theory of illegitimacy against the formal law, providing an understanding that an action, act, or activity is said to be against the law when against the rules set in the law. While through the Decision of the Supreme Court, Indonesia adheres to this theory. According to this theory, an action, act, or activity is said to be against the law when it is against the rules established in the law and according to the conditions is a disgraceful act or illegal. The decision of the Supreme Court provides the criteria for the loss of unlawful nature because of the factors of the state not being harmed, the society served and the defendant not making a profit. With the enactment of this theory, the existence of Article 4 of the Indonesian Corruption Law, becomes invalid with the condition that the results of corruption and its benefits have been returned by the perpetrators of corruption.